Meningkatkan Aktivitas dan Hasil Belajar Matematika Melalui Strategi Pembelajaran TAPPS Berbasis Pendekatan (STEM) - Meri Hari Yanni (Jurnal Pendidikan Matematika:Judika Education, 2018)
This study aimed to improve the activity and learning outcome of the eighth grade students of Al-Ulum Islamic school Medan through the TAPPS learning strategy based on STEM education. The research method was a classroom action research as much as two cycles. Each cycle consisted of 4 stages: planning, action, observation, and reflection. The data analysis technique was a descriptive analysis model. Data collection methods were observation and tests. The results showed that the implementation of using the STEM-based TAPPS learning strategy could improve learning activity of the eighth grade student of Al-Ulum Islamic school Medan on the subject of geometry flat side (Bangun Ruang Sisi Datar). This was shown by the percentage of group activity of students in the cycle I was 50.71% or in a good category, the percentage of student group activity in the cycle II was 85.04% or in an excellent category. Thus, the enhancement of students' learning activity using the TAPPS learning strategy based on STEM education could also improve students' learning outcome. This was shown by the percentage of learning mastery in the cycle I was 65,6255% or in the criteria of learning mastery was achieved but it was still classified as low and the percentage of learning mastery, in the cycle II was 90,625% or in the criteria of leaening mastery was achieved. The conclusion of this study is the use of TAPPS-based STEM education learning strategy can improve the activity and learning outcome of students. Keyword: TAPPS strategy,STEM education, activities, students' learningout come